Cerebrospinal fluid-based boron delivery system may help increase the uptake boron for boron neutron capture therapy in veterinary medicine: A preliminary study with normal rat brain cells. (November 2022) - Kusaka, Sachie; Morizane, Yuri; Tokumaru, Yugo; Tamaki, Shingo; Maemunah, Indah Rosidah; Akiyama, Yoko; Sato, Fuminobu; Murata, Isao
Abstract: Boron neutron capture therapy (BNCT) is a non-invasive type of radiation therapy developed for humans and translated to veterinary medicine. However, clinical trials on BNCT for patients with brain tumors are on-going. To improve the therapeutic efficacy of BNCT for brain tumors, we developed a boron delivery system that involves the cerebrospinal fluid (CSF), in contrast to the conventional method that involves intravenous (IV) administration. This study aimed to investigate the time-concentration profile of boron in the CSF as well as the uptake rate of boron by the brain cells after administering L-p‑boronophenylalanine (BPA) into the lateral ventricle of normal rats. Brain cell uptake rates were compared between the CSF-based and IV administration methods. The CSF-based and IV administration methods achieved comparable brain cell uptake levels; however, the former method involved lower BPA doses than the latter method. These findings suggest that the CSF method may reduce the economic and physical burdens associated with this treatment in brain tumor patients. Future studies should validate these findings in rat models of brain tumors. Highlights: CSF-based drug delivery may help by-pass the blood-brain barrier in boron neutron capture therapy. Brain cell boron levels achieved with the CSF-based and IV methods were similar. CSF-based method may improve treatment delivery. This method may reduce toxicity risks and treatment costs.